Gambaran Tingkat Pengetahuan Ibu dalam Mendeteksi Dini Demam Berdarah Dengue pada Anak Usia 5–14 Tahun di Desa Paseban, Kabupaten Klaten - Wahyu Putri Lestari; Fida’ Husain (Pusat Riset dan Inovasi Nasional, 2025)
The increase in dengue fever (DHF) cases in 2024 has become a serious global concern, with 14 million cases and over 10,000 deaths reported worldwide. In Indonesia, children aged 5–14 years are the most affected group, with 138,465 cases. Mothers play a crucial role in preventing DHF in children. Mothers with good knowledge of early signs and symptoms can help ensure faster treatment and prevent severe complications. Objective: This study aims to describe the level of mothers' knowledge in detecting early signs of DHF in children aged 5–14 years in Paseban Village, Klaten Regency. Method: This is a descriptive quantitative study using purposive sampling. The population consisted of 699 mothers with children aged 5–14 years, and 100 respondents were selected as samples. A questionnaire with 29 validated and reliable items was used as the research instrument. Results: Most mothers (76%) in Paseban Village had good knowledge of early DHF detection. Implication: These findings suggest that most mothers are already well-informed about recognizing early symptoms of DHF. This reflects the positive impact of health education provided through health workers and media, which should be continued and expanded to strengthen DHF prevention efforts.